Transformative Learning in the Era of Post-Reflexivity - Fabbri, Loretta (Adult Education Critical Issues, 2024)
This article collects over 20 years of studies, encounters, and conversations around Transformative Theory and reflective practices, which have characterized my identity as a scholar and the Italian Transformative Learning Network’s identity. I am going to trace the main challenges that, starting from practice-based studies and situated learning theory, have established the foundation for our research group's discussion on Transformative Learning. I am going to venture into open dialectical arenas with new perspectives that have amazed and questioned me. The posthuman, sociomateriality, and post-qualitative inquiry interrogate some of the foundations of Transformative Theory and urge us to create a creative space to share challenging epistemic constructions.